Concept of Happiness in Islam - Mohammad Hanief Sirajulhuda (Penerbit Presisi Pustaka, 2025)
Happiness in today's world does not only touch worldly (secular) life, because it has a relationship with worldly life as interpreted and guided by religion that originates from revelation. The happiness of the afterlife and this world must be pursued in the corridors of revelation. So, it can be understood that true happiness can only be achieved with knowledge accompanied by faith. That is why Al-Sa'di stated that to achieve happiness you need religious, natural and practical means that cannot be achieved except by a believer. A calm soul, based on this concept, is caused by the establishment of strong faith as a foundation in the soul, based on true knowledge, then accompanied by the continuous implementation of good deeds that will cleanse and purify the soul.